Mempertahankan Eksistensi Pemasaran Batik Tulis Pamekasan Selama Pandemi Covid-19 pada Kelompok Pengrajin Nyi Leha Batik - Fawaid, Akh. (Universitas Nusantara PGRI Kediri, 2022)
The Covid-19 pandemic threatens the sustainability of the income of written batik craftsmen and sellers in Pamekasan Regency. Moreover, most of the marketing systems used still use the conventional system (face-to-face seller-buyer). As a result, the income of Pamekasan batik craftsmen and sellers has dropped dramatically. Advances in technology have enabled the Nyi Leha Batik craftsman group located in Arsojih Hamlet, Pagendingan Village, Galis District, Pamekasan Regency, to change their marketing patterns using digital marketing. The goal is to encourage Pamekasan batik craftsmen and sellers to develop their marketing patterns using digital marketing patterns. The target is to make marketing easier and increase revenue. The method used in achieving these goals is through a comprehensive approach and effort in marketing training methods, methods assistance in taking product photos through counseling and training by way of direct demonstrations and using the website in the promotion and sale of products. In order to achieve this, through training and digital marketing workshops (digital marketing). Including training and mentoring for marketing and promotion strategies, uploud products, to business management training and assistance in the preparation of business plans.